Politik Hukum Islam di Indonesia pada Masa Kolonial Jepang : Politisasi & Militerisasi - Ilhami, Hanif A'la; Amin, Saiful; Fahmi, Khairul; A’la Ilhami, Hanif (JURNAL TAPIS, 2024)
This paper delineates the various policies implemented by the Japanese colonialadministration in regulating Islam in Indonesia. Utilizing a qualitative research approach, it draws upon library sources for its data. The study reveals that Japan, much like the Netherlands, aimed to exploit Indonesia's resources for its own needs. However, the policies of the two colonial powers were sometimes diametrically opposed, particularly in their approach to the Muslim population. While the Dutch sought to subdue Muslims by severing ties, isolating, and halting Islamic movements, viewing them as adversaries, the Japanese adopted a contrasting strategy. Japan endeavored to pacify Muslims by creating a calmeratmosphere, persuading, and embracing Islamic movements to position them as allies, or at least neutral entities. Although Japanese colonial rule continued to oppress and exploit Muslims similarly to the Dutch, it afforded them valuable opportunities to participate in political movements and military education opportunities that were entirely absent during Dutch colonial rule.